Structure and dynamics of the contractile vacuole complex in Tetrahymena thermophila - Cheng, Chao-Yin; Romero, Daniel P; Zoltner, Martin; Yao, Meng-Chao; Turkewitz, Aaron P (Journal of cell science, 2023)
The contractile vacuole complex (CVC) is a dynamic and morphologically complex membrane organelle, comprising a large vesicle (bladder) linked with a tubular reticulum (spongiome). CVCs provide key osmoregulatory roles across diverse eukaryotic lineages, but probing the mechanisms underlying their structure and function is hampered by the limited tools available for in vivo analysis. In the experimentally tractable ciliate Tetrahymena thermophila, we describe four proteins that, as endogenously tagged constructs, localize specifically to distinct CVC zones. The DOPEY homolog Dop1p and the CORVET subunit Vps8Dp localize both to the bladder and spongiome but with different local distributions that are sensitive to osmotic perturbation, whereas the lipid scramblase Scr7p colocalizes with Vps8Dp. The H+-ATPase subunit Vma4 is spongiome specific. The live imaging permitted by these probes revealed dynamics at multiple scales including rapid exchange of CVC-localized and soluble protein pools versus lateral diffusion in the spongiome, spongiome extension and branching, and CVC formation during mitosis. Although the association with DOP1 and VPS8D implicate the CVC in endosomal trafficking, both the bladder and spongiome might be isolated from bulk endocytic input.
Keywords: vakuoly; Mitosis; mitóza; Organelle dynamics; endozomy; Vacuoles; Tetrahymena; Tetrahymena thermophila; Endosomes; Contractile vacuole complex; Proteins; Organelle biogenesis; proteiny; Osmotic regulation